First detection and molecular characterization of Nebovirus in Brazil - Candido, M.; Alencar, A. L.F.; Almeida-Queiroz, S. R.; Buzinaro, M. G. [UNESP]; Munin, F. S.; Godoy, S. H.S.; Livonesi, M. C.; Fernandes, A. M.; Sousa, R. L.M. (Cambridge University Press (CUP), 2016)
Nebovirus is a new genus of viruses belonging to the Caliciviridae family recently characterized in cattle, and is associated with gastrointestinal disorders, such as diarrhoea, anorexia and intestinal lesions particularly in calves. The aim of this study was to investigate the prevalence of neboviruses in Brazilian cattle and analyse phylogenetically the virus strains detected. A prevalence of 4·8% of neboviruses in faecal samples from 62 head of cattle from different Brazilian states was detected. All positive animals were aged <20 days and had diarrhoea. Phylogenetic analysis clustered the virus sequences into the Newbury1 clade. There was >96·0% nt (100% aa) sequence identity between the virus sequences in this study and >88·8% nt (>94·4% aa) identity with Newbury1/UK. Our results indicate, for the first time, the occurrence of neboviruses in Brazil as well as in South America, and the first Newbury1-like nebovirus found outside the UK.
Keywords: Caliciviridae; cattle diseases; diarrhoea; molecular epidemiology